Integrating biodiversity into land-use regulations: Evidence from Swiss municipal plan revisions - Stephanie Schwab Cammarano; Marco Moretti; Rolf Holderegger; Florian Altermatt; Anna M. Hersperger (Urban Forestry & Urban Greening, 2026)

Navigating urban ecology: Conceptual and methodological insights - Ian MacGregor‐Fors; Christine C. Rega‐Brodsky; D. Johan Kotze; J. Scott MacIvor; Amy K. Hahs; Marco Moretti; Nicholas S. G. Williams; Christopher A. Lepczyk; Kirsten Jung; Madhusudan Katti; Sonja Knapp; Frank A. La Sorte; et al. (Ecology, 2026)
Since its consolidation as a sub‐discipline of ecology in the late 1990s, urban ecology has grown substantially, enhancing our understanding of how urbanization shapes biodiversity and how biodiversity adapts to urbanization. Inherently interdisciplinary in its scope and application, urban ecology is rooted in multiple theoretical and methodological foundations, potentially making the field overwhelming for newcomers as the key literature is scattered across multiple disciplines. Drawing on the collective expertise of editors and reviewers, we attempt to address common pitfalls noted in studies of biodiversity within urban ecosystems and suggest action items for both the new and experienced urban ecologist. Here, we present key concepts for framing hypothesis‐based urban biodiversity research questions, conceptualizing urban settings, accounting for spatial and temporal scales, selecting study systems and meaningful explanatory variables for research questions, and recognizing the social‐ecological nature of urban systems. We offer insights and examples, emphasizing the importance of rigorous urban ecological research without imposing constraints on innovation.

Non-linear responses of ecological indicators to urban environmental drivers across Europe - Bernardo Rocha; Paula Matos; Paolo Giordani; Joan Casanelles-Abella; Marco Moretti; Nicolas Deguines; Lauri Laanisto; Marta Alos Orti; Piotr Tryjanowski; Tiit Hallikma; Cristina Branquinho; Pedro Pinho (Journal of Environmental Management, 2026)

Enhancing prioritization strategies of natural extracts: integrating heterogeneous data from metabolomics datasets and biological screenings into knowledge graphs - Luis-Manuel Quiros-Guerrero; Frederic Burdet; Olivier Kirchhoffer; Paola Haemmerli; Louis-Felix Nothias; Pierre-Marie Allard; Arnaud Gaudry; Jahn Nitschke; Nabil Hanna; Sébastien Moretti; Robin Engler; Florence Mehl; et al. (Phytochemistry Letters, 2025)

Grassland duration affects soil organic carbon pools only in the topsoil and has limited effects on microbial metabolism - Claudia Dămătîrcă; Barbara Moretti; Laura Zavattaro; Julia Schroeder; Christopher Poeplau; Alexandra Ciorîţă; Marco Pittarello; Luisella Celi; Giampiero Lombardi (Agriculture, Ecosystems & Environment, 2025)

Green roofs harbor different and non-substituting invertebrate communities than surrounding ground-level habitats - Kilian Perrelet; Marco Moretti; Océane Inglard; Florian Altermatt; Lauren M. Cook (Journal of Environmental Management, 2025)

Urbanisation Drives the Decoupling, Simplification, and Homogenization of Aquatic and Terrestrial Food Webs - Kilian Perrelet; Lauren M. Cook; Merin Reji Chacko; Florian Altermatt; Marco Moretti (Ecology Letters, 2025)
Aquatic and terrestrial communities often co‐occur at close distances, enabling biotic interactions across ecosystem boundaries. While such interactions in natural habitats contribute to complex, coupled food webs, their dynamics in engineered and fragmented urban habitats are hardly known. Using environmental DNA metabarcoding and a metaweb approach, we examined food web structure at 54 paired aquatic‐terrestrial sites along an urbanisation gradient in Zurich, Switzerland. We found that urbanisation led to simpler, less connected, and more homogeneous food webs by replacing high‐trophic‐level predators with low‐trophic‐level basal consumers. This shift towards basal consumers, dependent on distinct aquatic or terrestrial basal resources, subsequently weakened the links between aquatic and terrestrial food webs. Conversely, enhancing habitat quantity and landscape connectivity bolstered predator diversity, promoting vertically diverse, connected, complex, and stable food webs. Our findings reveal that while urbanisation can disrupt aquatic‐terrestrial food webs, careful urban habitat planning can enhance biodiversity and food web stability.

Aquatic and terrestrial environmental DNA signals reveal decoupling of blue-green communities along an urbanization gradient - Kilian Perrelet; Lauren M. Cook; Andreas Dietzel; Florian Altermatt; Marco Moretti (Landscape and Urban Planning, 2025)

Value chains for sustainable mountain development: a qualitative understanding of 23 European cases - Kirsty Blackstock; Rachel Creaney; Mar del Mar Delgado-Serrano; Sharon Flanigan; Corrado Ievoli; Michele Moretti; Gusztáv Nemes; Diana Surovà; Chloe Thompson; Lukas Zagata; Tarek Allali; Angelo Belliggiano; et al. (Journal of Rural Studies, 2025)

Pollinator‐Promoting Interventions in European Urban Habitats—A Synthesis - Gabriella Süle; András Báldi; David Kleijn; Ingolf Steffan‐Dewenter; Stephen Venn; Dave Goulson; Simon Dietzel; Audrey Muratet; Lorna J. Cole; Erik Öckinger; Olga Tzortzakaki; Weronika Banaszak‐Cibicka; et al. (Ecology Letters, 2025)
Pollinators receive considerable interest due to their fundamental role in ecosystem functioning and human well‐being. Unlike farmlands, studies of urban pollinator‐promoting interventions are scarce and have not been synthesised, hampering policy implementation. To fill this gap, we compared pollinator‐promoting interventions (treatment) with conventionally managed (control) sites regarding vegetation, floral resources, and pollinators. Our synthesis investigated 1051 sampling sites with different interventions (abandonment, extensive mowing, flower sowing, and combined practices) and habitats (parks, grasslands, road verges, private and public gardens) from 28 European datasets at pooled‐ and study‐levels. Urban pollinator‐promoting interventions generally benefited plants and pollinators with taxon, intervention, habitat, and spatio‐temporal specific differences. Pooled analyses showed mostly positive and never negative treatment effects, while study‐level details described primarily positive and neutral but rarely negative effects. Bumblebees and butterflies benefited most from the interventions. Some effects were stronger for interventions involving flower sowing, interventions occurring in road verges, and interventions located in Northwestern Europe. Although regulations, guidelines, and monitoring are improving, knowledge gaps remain for some pollinator taxa (e.g., beetles), regions (e.g., Mediterranean), and novel interventions (e.g., for ground‐nesting insects). Further collaborative studies from around the world could help cities bring people, plants, and pollinators together by creating resilient, multi‐functional urban spaces.

MRI-guided stereotactic radiotherapy for oligometastatic peritoneal carcinomatosis: toward integrative oncologic approaches - Angela Romano; Giuditta Chiloiro; Luca Boldrini; Giulia Panza; Ilaria Castanò; Maura Campitelli; Isabella Costamagna; Irene Moretti; Matteo Nardini; Marco Valerio Antonelli; Claudio Votta; Lorenzo Placidi; et al. (Clinical & Experimental Metastasis, 2025)

Effect of simulated prolonged heat wave on biometric performance and HSP70 synthesis in the striped venus clam Chamelea gallina - Antonina De Marco; Vito Antonio Baldassarro; Maura Cescatti; Marzia Moretti; Laura Calzà; Luciana Giardino; Francesco Dondi; Maria Giulia Ferrari; Pier Paolo Gatta; Luca Parma; Alessio Bonaldo (Aquaculture, 2025)

Spatial and seasonal trait selection in dung beetle assemblages along an aridity gradient in the Sahara - Indradatta de Castro‐Arrazola; Francisco Sánchez‐Piñero; Marco Moretti; Joaquín Hortal (Ecology, 2025)
Ecological communities under extreme environments are shaped by a balance of environmental filtering and coexistence mechanisms that result in a series of assembly rules. Although there is abundant evidence about the importance of these community assembly mechanisms in plants, their effects have been seldom compared for animals. We assess their relative importance for the temporal and spatial responses of dung beetle communities along a strong aridity gradient in the edge of the Sahara. Specifically, we study how phylogenetic and functional community structure varies with aridity in space and time and combine it with selected traits to assess the relative importance of mechanisms associated with known assembly rules along the gradient, including whether increasing aridity selects for specific trait values. We surveyed a 400‐km gradient toward the Sahara in the dry and wet seasons of two consecutive years, gathering phylogenetic information and quantifying traits related to aridity from direct measurements and the literature. We calculated metrics of functional and phylogenetic diversity, the decoupled variation in functional diversity, functional and phylogenetic beta diversity, their standardized effect sizes based on null models, and community weighted means for all relevant traits. Then, we assessed the relationships between the spatial and temporal variations in these facets of diversity through linear models, independent principal components analyses, and multiple ANOVAs (MANOVAs). Increasing aridity filters dung beetle communities at the phylogenetic and functional levels, selecting particular trait syndromes in both space and time, as communities change similarly toward the Sahara and between the wet and dry seasons. Contrary to expectations, phylogenetic and functional structure shows a continuous replacement with aridity rather than a nested loss of lineages and trait values, which is not accompanied by a reduction in trait volume along the gradient. Only the hyperarid conditions of the dry season show reductions in trait volume. This implies that responses to aridity lead to assemblages with a common adaptive strategy, dominated by saprophagous species with longer wings and endocoprid behavior, associated with the acquisition of ephemeral resources in the poor desert environment. In addition, animal communities can respond to rapid ecosystem breakdowns if their phenological amplitude includes extreme conditions.

Factors influencing nitrogen derived from soil organic matter mineralisation: Results from a long-term experiment - Octavian P. Chiriac; Marco Pittarello; Barbara Moretti; Laura Zavattaro (Agriculture, Ecosystems & Environment, 2025)

The urban in ecology: a quantitative textual analysis of the scientific literature over a century - Silvia Flaminio; Joëlle Salomon Cavin; Guillaume Guex; Marco Moretti (Urban Ecosystems, 2024)
Many authors have described ‘urban ecology’ as a subfield of ecology that emerged in the 1990s and has expanded exponentially. We propose to take a step further and analyse the expansion of the ‘urban’ in ecology with a novel quantitative approach, with the aim to better understand the relationship between ecology and the urban. Previous quantitative assessments of the urban in ecology have focused on short to medium time spans (5 to 40 years) and on research coined as ‘urban ecology’, and have rarely considered the content of publications (e.g., vocabulary and topics) using quantitative methods. In this paper, we conduct a bibliometric assessment and an in-depth quantitative textual data analysis of a corpus of 960 articles published from 1922 to 2018 in 10 leading English-language journals in ecology and conservation biology. We address the following questions: (1) When and how have urban environments been integrated into ecological research during the past century? (2) What urban research topics have been investigated in ecology during the same period? (3) How have these research topics changed through time? Our results show that the urban was never entirely absent from publications in ecology. The quantitative analyses highlight three turning points (1970s, 1990s and 2000s) in the relationship between ecology and the urban. Moreover, they help visualize the shift from particularly scattered publications at the beginning of the period to publications characterized by a more homogeneous vocabulary, reflecting the stabilization of a research field focused on the urban in ecology.

Corrigendum to ‘Modelling the response of urban lichens to broad-scale changes in air pollution and climate’ [Environ. Pollut. 315 (2022) 120330] - Bernardo Rocha; Paula Matos; Paolo Giordani; Lõhmus Piret; Cristina Branquinho; Joan Casanelles-Abella; Cristiana Aleixo; Nicolas Deguines; Tiit Hallikma; Lauri Laanisto; Marco Moretti; Marta Alos Orti; et al. (Environmental Pollution, 2024)

The environmental and agronomic benefits and trade-offs linked with the adoption alternate wetting and drying in temperate rice paddies - Andrea Vitali; Barbara Moretti; Chiara Bertora; Eleonora Francesca Miniotti; Daniele Tenni; Marco Romani; Arianna Facchi; Maria Martin; Silvia Fogliatto; Francesco Vidotto; Luisella Celi; Daniel Said-Pullicino (Field Crops Research, 2024)

Interaction between water, crop residue and fertilization management on the source-differentiated nitrogen uptake by rice - Andrea Vitali; Federica Russo; Barbara Moretti; Marco Romani; Francesco Vidotto; Silvia Fogliatto; Luisella Celi; Daniel Said-Pullicino (Biology and Fertility of Soils, 2024)
Alternate wetting and drying (AWD) is an effective water-saving practice for rice cultivation that may however promote nitrogen (N) losses compared to continuous flooding (CF). The interaction between water, crop residue and N fertilization management can influence the contribution of different N sources to plant uptake. We hypothesized that microbial processes driving the source-differentiated N supply for rice uptake during the early growth stages will depend on the interaction between water management, the timing of straw incorporation with respect to flooding and the temporal distribution of mineral N application. Rice was grown for 60 days in mesocosm experiment involving a factorial design with (i) two water regimes (CF vs. AWD) and (ii) three straw and fertilizer managements, during which soil N, porewater chemistry, plant growth and N uptake were evaluated. Source partitioning of plant N between fertilizer-, straw- and soil-derived N was achieved by means of a dual-stable isotope 15 N tracing approach. Although AWD reduced total N uptake by about 4–25% with respect to CF, this could only be partly attributed to a lower uptake of fertilizer-N (and lower fertilizer-N use efficiency), suggesting that other N sources were affected by water management. Our findings evidence how the interaction between soil redox conditions and the availability of labile C and inorganic N strongly determined the supply of soil-derived N through microbial feedback and priming responses. Although incorporated straw contributed only minimally to rice N, it represented the primary driver controlling plant N nutrition through these microbial responses. These insights may contribute to identify suitable fertilization practices that favour plant N uptake during the early stages of rice growth under AWD.

First evidence of widespread positivity to anticoagulant rodenticides in grey wolves (Canis lupus) - Carmela Musto; Jacopo Cerri; Dario Capizzi; Maria Cristina Fontana; Silva Rubini; Giuseppe Merialdi; Duccio Berzi; Francesca Ciuti; Annalisa Santi; Arianna Rossi; Filippo Barsi; Luca Gelmini; et al. (Science of The Total Environment, 2024)

Conservation tillage in temperate rice cropping systems: Crop production and soil fertility - Andrea Vitali; Barbara Moretti; Cristina Lerda; Daniel Said-Pullicino; Luisella Celi; Marco Romani; Silvia Fogliatto; Francesco Vidotto (Field Crops Research, 2024)

How do urban green space designs shape avian communities? Testing the area–heterogeneity trade-off - François Chiron; Romain Lorrillière; Carmen Bessa-Gomes; Piotr Tryjanowski; Joan Casanelles-Abella; Lauri Laanisto; Ana Leal; Anskje Van Mensel; Marco Moretti; Babette Muyshondt; Ülo Niinemets; Marta Alós Ortí; et al. (Landscape and Urban Planning, 2024)

Spatial mismatch between wild bee diversity hotspots and protected areas - Joan Casanelles‐Abella; Simone Fontana; Eliane Meier; Marco Moretti; Betrand Fournier (Conservation Biology, 2023)
Wild bees are critical for multiple ecosystem functions but are currently threatened. Understanding the determinants of the spatial distribution of wild bee diversity is a major research gap for their conservation. We modeled wild bee α and β taxonomic and functional diversity in Switzerland to uncover countrywide diversity patterns and determine the extent to which they provide complementary information, assess the importance of the different drivers structuring wild bee diversity, identify hotspots of wild bee diversity, and determine the overlap between diversity hotspots and the network of protected areas. We used site‐level occurrence and trait data from 547 wild bee species across 3343 plots and calculated community attributes, including taxonomic diversity metrics, community mean trait values, and functional diversity metrics. We modeled their distribution with predictors describing gradients of climate, resource availability (vegetation), and anthropogenic influence (i.e., land‐use types and beekeeping intensity). Wild bee diversity changed along gradients of climate and resource availability; high‐elevation areas had lower functional and taxonomic α diversity, and xeric areas harbored more diverse bee communities. Functional and taxonomic β diversities diverged from this pattern, with high elevations hosting unique species and trait combinations. The proportion of diversity hotspots included in protected areas depended on the biodiversity facet, but most diversity hotspots occurred in unprotected land. Climate and resource availability gradients drove spatial patterns of wild bee diversity, resulting in lower overall diversity at higher elevations, but simultaneously greater taxonomic and functional uniqueness. This spatial mismatch among distinct biodiversity facets and the degree of overlap with protected areas is a challenge to wild bee conservation, especially in the face of global change, and calls for better integrating unprotected land. The application of spatial predictive models represents a valuable tool to aid the future development of protected areas and achieve wild bee conservation goals.

A geophysical multidisciplinary approach to investigate the shallow subsoil structures in volcanic environment: The case of Ischia Island - Lucia Nardone; Maurizio Vassallo; Giovanna Cultrera; Vincenzo Sapia; Simona Petrosino; Marta Pischiutta; Mauro Di Vito; Sandro de Vita; Danilo Galluzzo; Giuliano Milana; Eliana Bellucci Sessa; Antonella Bobbio; et al. (Journal of Volcanology and Geothermal Research, 2023)

Avoid, tolerate, or escape? Native vegetation responses to invasion vary between functional groups - Marie Charlotte Grange; François Munoz; Marco Moretti; Sylvain Varona-Y-Varona; Julien Renaud; Marie-Pascale Colace; Maya Gueguen; Cindy Arnoldi; Lionel Bernard; Laure Gallien (Biological Invasions, 2023)

The magnetic signal from trunk bark of urban trees catches the variation in particulate matter exposure within and across six European cities - Anskje Van Mensel; Karen Wuyts; Pedro Pinho; Babette Muyshondt; Cristiana Aleixo; Marta Alos Orti; Joan Casanelles-Abella; François Chiron; Tiit Hallikma; Lauri Laanisto; Marco Moretti; Ülo Niinemets; et al. (Environmental Science and Pollution Research, 2023)

Features of post-obstructive pneumonia in advanced lung cancer patients, a large retrospective cohort - Marco Moretti; Shauni Wellekens; Silke Dirkx; Karolien Vekens; Johan Van Laethem; Bart Ilsen; Eef Vanderhelst (Infectious Diseases, 2023)

Emission estimates and air quality simulation on Lombardy during lockdown - Alessandro Marongiu; Elisabetta Angelino; Giulia Malvestiti; Marco Moretti; Giuseppe Fossati; Edoardo Peroni (Air Quality, Atmosphere & Health, 2023)

Urban forest invertebrates: how they shape and respond to the urban environment - D. Johan Kotze; Elizabeth C. Lowe; J. Scott MacIvor; Alessandro Ossola; Briony A. Norton; Dieter F. Hochuli; Luis Mata; Marco Moretti; Sara A. Gagné; I. Tanya Handa; Therésa M. Jones; Caragh G. Threlfall; et al. (Urban Ecosystems, 2022)
Invertebrates comprise the most diversified animal group on Earth. Due to their long evolutionary history and small size, invertebrates occupy a remarkable range of ecological niches, and play an important role as “ecosystem engineers” by structuring networks of mutualistic and antagonistic ecological interactions in almost all terrestrial ecosystems. Urban forests provide critical ecosystem services to humans, and, as in other systems, invertebrates are central to structuring and maintaining the functioning of urban forests. Identifying the role of invertebrates in urban forests can help elucidate their importance to practitioners and the public, not only to preserve biodiversity in urban environments, but also to make the public aware of their functional importance in maintaining healthy greenspaces. In this review, we examine the multiple functional roles that invertebrates play in urban forests that contribute to ecosystem service provisioning, including pollination, predation, herbivory, seed and microorganism dispersal and organic matter decomposition, but also those that lead to disservices, primarily from a public health perspective, e.g., transmission of invertebrate-borne diseases. We then identify a number of ecological filters that structure urban forest invertebrate communities, such as changes in habitat structure, increased landscape imperviousness, microclimatic changes and pollution. We also discuss the complexity of ways that forest invertebrates respond to urbanisation, including acclimation, local extinction and evolution. Finally, we present management recommendations to support and conserve viable and diverse urban forest invertebrate populations into the future.

Wild bee larval food composition in five European cities - Joan Casanelles‐Abella; Alexander Keller; Stefanie Müller; Cristiana Aleixo; Marta Alós‐Orti; François Chiron; Lauri Laanisto; Łukasz Myczko; Pedro Pinho; Roeland Samson; Piotr Tryjanowski; Anskje Van Mensel; et al. (Ecology, 2022)
Urbanization poses threats and opportunities for the biodiversity of wild bees. At the same time, cities can harbor diverse wild bee assemblages, partly due to the unique plant assemblages that provide resources. While bee dietary preferences have been investigated in various studies, bee dietary studies have been conducted mostly in nonurban ecosystems and data based on plant visitation observations or palynological techniques. This data set describes the larval food preferences of four wild bee species (i.e., Chelostoma florisomne , Hylaeus communis , Osmia bicornis , and O. cornuta ) common in urban areas in five different European cities (i.e., Antwerp, Belgium; Paris, France; Poznan, Poland; Tartu, Estonia; and Zurich, Switzerland). In addition, the data set describes the larval food preferences of individuals from three wild bee genera (i.e., Chelostoma sp., Hylaeus sp., and Osmia sp.) that could not be identified to the species level. These data were obtained from a Europe‐level study aimed at understanding the effects of urbanization on biodiversity across different cities and cityscapes and a Swiss project aimed at understanding the effects of urban ecosystems in wild bee feeding behavior. Wild bees were sampled using standardized trap nests at 80 sites (32 in Zurich and 12 in each of the remaining cities), selected following a double gradient of available habitat at local and landscape scales. Larval pollen was obtained from the bee nests and identified using DNA metabarcoding. The data provide the plant composition at the species or genus level preferred by each bee. These unique data can be used for a wide array of research questions, including urban ecology (e.g., diversity of food sources along urban gradients), bee ecology (characterization of bee feeding preferences), or comparative studies on the urban evolution of behavioral traits between urban and nonurban sites. In addition, the data can be used to inform urban planning and conservation strategies, particularly concerning flower resources (e.g., importance of exotic species and, thus, management activities). This data set can be freely used for noncommercial purposes, and this data paper should be cited if the data is used; we request that collaboration with the data set contact person to be considered if this data set represents an important part of the data analyzed in a study.

Urban biodiversity: State of the science and future directions - Christine C. Rega-Brodsky; Myla F. J. Aronson; Max R. Piana; Ela-Sita Carpenter; Amy K. Hahs; Adriana Herrera-Montes; Sonja Knapp; D. Johan Kotze; Christopher A. Lepczyk; Marco Moretti; Allyson B. Salisbury; Nicholas S. G. Williams; et al. (Urban Ecosystems, 2022)

Diagnostic accuracy of screening tests for patients suspected of COVID-19, a retrospective cohort study - Marco Moretti; Johan Van Laethem; Deborah De Geyter; Wilfried Cools; Bart Ilsen; Sabine Danielle Allard; Denis Pierard (Infectious Diseases, 2021)

Direct and Indirect Effects of Forest Anthropogenic Disturbance on Above and Below Ground Communities and Litter Decomposition - Idaline Laigle; Marco Moretti; Laurent Rousseau; Dominique Gravel; Lisa Venier; I. Tanya Handa; Christian Messier; Dave Morris; Paul Hazlett; Rob Fleming; Kara Webster; Bill Shipley; et al. (Ecosystems, 2021)

Reconciling trait based perspectives along a trait‐integration continuum - Simone Fontana; Sergio Rasmann; Francesco de Bello; Francesco Pomati; Marco Moretti (Ecology, 2021)
Trait based ecology has developed fast in the last decades, aiming to both explain mechanisms of community assembly, and predict patterns in nature, such as the effects of biodiversity shifts on key ecosystem processes. This body of work has stimulated the development of several conceptual frameworks and analytical methods, as well as the production of trait databases covering a growing number of taxa and organizational levels (from individuals to guilds). However, this breeding ground of novel concepts and tools currently lacks a general and coherent framework, under which functional traits can help ecologists organize their research aims, and serve as the common currency to unify several scientific disciplines. Specifically, we see a need to bridge the gaps between community ecology, ecosystem ecology, and evolutionary biology, in order to address the most pressing environmental issues of our time. To achieve this integration goal, we define a trait‐integration continuum, which reconciles alternative trait definitions and approaches in ecology. This continuum outlines a coherent progression of biological scales, along which traits interact and hierarchically integrate from genetic information, to whole organism fitness‐related traits, to trait syndromes and functional groups. Our conceptual scheme proposes that lower‐level trait integration is closer to the inference of ecoevolutionary mechanisms determining population and community properties, whereas higher‐level trait integration is most suited to the prediction of ecosystem processes. Within these two extremes, trait integration varies on a continuous scale, which relates directly to the inductive‐deductive loop that should characterize the scientific method. With our proposed framework, we aim to facilitate scientists in contextualising their research based on the trait‐integration levels that matter most to their specific goals. Explicitly acknowledging the existence of a trait‐integration continuum is a promising way for framing the appropriate questions, thus obtaining reliable answers and results that are comparable across studies and disciplines.

Behavioural and pharmacological profiles of zebrafish administrated pyrrolidinyl benzodioxanes and prolinol aryl ethers with high affinity for heteromeric nicotinic acetylcholine receptors - Daniela Braida; Luisa Ponzoni; Milena Moretti; Paola Viani; Marco Pallavicini; Cristiano Bolchi; Rebecca Appiani; Francesco Bavo; Cecilia Gotti; Mariaelvina Sala (Psychopharmacology, 2020)

Correction to: Genetic diversity and reproductive ecology of the sage-leaved rockrose, Cistus salviifolius L., in the Swiss Alps - Marco Moretti; Paolo Caretti; Anya Bricalli; Marco Andrello (Plant Ecology, 2020)

Genetic diversity and reproductive ecology of the sage-leaved rockrose, Cistus salviifolius L., in the Swiss Alps - Marco Moretti; Paolo Caretti; Anya Bricalli; Marco Andrello (Plant Ecology, 2020)

Niche breadth of invertebrate shredders in tropical forest streams: which taxa have restricted habitat preferences? - Karoline Victor Serpa; Walace Pandolpho Kiffer; Miliane Fardim Borelli; Marcos Antônio Ferraz; Marcelo S. Moretti (Hydrobiologia, 2020)

The origin of urban communities: From the regional species pool to community assemblages in city - Bertrand Fournier; David Frey; Marco Moretti (Journal of Biogeography, 2020)
Aim Cities worldwide are characterized by unique human stressors that filter species based on their traits, potentially leading to biodiversity loss. The knowledge of which species are filtered and at which scale is important to gain a more mechanistic understanding of urban community assembly and to develop strategies to manage human impact on urban ecosystems. We investigate the ecological mechanisms shaping urban community assembly, taking into account changes across scales, taxa and urban green space types. Location City of Zurich, Switzerland. Taxon Carabid beetles and wild bees. Methods We use a large species occurrence and trait dataset with a high spatial resolution to assess the filtering effect of a medium‐sized city on a regional pool of potential colonists. We then assess the filtering from the urban pool to five widely distributed types of urban green spaces. Results We found that our model city selects for functionally similar but taxonomically diverse bee and carabid beetle species from the regional species pool. Within the city, community assembly processes vary among green space types and taxa resulting in important changes in community taxonomic and functional composition. Main conclusions Our findings suggest that urban community assembly is a multi‐scale process dominated by the strong environmental filtering from a regional to an urban species pool. This leads to the selection of species pre‐adapted to urban conditions. Spatial habitat heterogeneity within and among UGS types can maintain an important taxonomic diversity within cities. However, increasing urban functional diversity would require stronger management efforts that consider regional ecological processes.

Similar factors underlie tree abundance in forests in native and alien ranges - Masha T. van der Sande; Helge Bruelheide; Wayne Dawson; Jürgen Dengler; Franz Essl; Richard Field; Sylvia Haider; Mark van Kleunen; Holger Kreft; Joern Pagel; Jan Pergl; Oliver Purschke; et al. (Global Ecology and Biogeography, 2020)
Aim Alien plant species can cause severe ecological and economic problems, and therefore attract a lot of research interest in biogeography and related fields. To identify potential future invasive species, we need to better understand the mechanisms underlying the abundances of invasive tree species in their new ranges, and whether these mechanisms differ between their native and alien ranges. Here, we test two hypotheses: that greater relative abundance is promoted by (a) functional difference from locally co‐occurring trees, and (b) higher values than locally co‐occurring trees for traits linked to competitive ability. Location Global. Time period Recent. Major taxa studied Trees. Methods We combined three global plant databases: sPlot vegetation‐plot database, TRY plant trait database and Global Naturalized Alien Flora (GloNAF) database. We used a hierarchical Bayesian linear regression model to assess the factors associated with variation in local abundance, and how these relationships vary between native and alien ranges and depend on species’ traits. Results In both ranges, species reach highest abundance if they are functionally similar to co‐occurring species, yet are taller and have higher seed mass and wood density than co‐occurring species. Main conclusions Our results suggest that light limitation leads to strong environmental and biotic filtering, and that it is advantageous to be taller and have denser wood. The striking similarities in abundance between native and alien ranges imply that information from tree species’ native ranges can be used to predict in which habitats introduced species may become dominant.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Effects of garden management practices, by different types of gardeners, on human wellbeing and ecological and soil sustainability in Swiss cities - Robert Home; Olivia Lewis; Nicole Bauer; Andreas Fliessbach; David Frey; Stéphanie Lichtsteiner; Marco Moretti; Simon Tresch; Christopher Young; Andrea Zanetta; Matthias Stolze (Urban Ecosystems, 2019)

Biotic interactions in species distribution modelling: 10 questions to guide interpretation and avoid false conclusions - Carsten F. Dormann; Maria Bobrowski; D. Matthias Dehling; David J. Harris; Florian Hartig; Heike Lischke; Marco D. Moretti; Jörn Pagel; Stefan Pinkert; Matthias Schleuning; Susanne I. Schmidt; Christine S. Sheppard; et al. (Global Ecology and Biogeography, 2018)
Aim Recent studies increasingly use statistical methods to infer biotic interactions from co‐occurrence information at a large spatial scale. However, disentangling biotic interactions from other factors that can affect co‐occurrence patterns at the macroscale is a major challenge. Approach We present a set of questions that analysts and reviewers should ask to avoid erroneously attributing species association patterns to biotic interactions. Our questions relate to the appropriateness of data and models, the causality behind a correlative signal, and the problems associated with static data from dynamic systems. We summarize caveats reported by macroecological studies of biotic interactions and examine whether conclusions on the presence of biotic interactions are supported by the modelling approaches used. Findings Irrespective of the method used, studies that set out to test for biotic interactions find statistical associations in species’ co‐occurrences. Yet, when compared with our list of questions, few purported interpretations of such associations as biotic interactions hold up to scrutiny. This does not dismiss the presence or importance of biotic interactions, but it highlights the risk of too lenient interpretation of the data. Combining model results with information from experiments and functional traits that are relevant for the biotic interaction of interest might strengthen conclusions. Main conclusions Moving from species‐ to community‐level models, including biotic interactions among species, is of great importance for process‐based understanding and forecasting ecological responses. We hope that our questions will help to improve these models and facilitate the interpretation of their results. In essence, we conclude that ecologists have to recognize that a species association pattern in joint species distribution models will be driven not only by real biotic interactions, but also by shared habitat preferences, common migration history, phylogenetic history and shared response to missing environmental drivers, which specifically need to be discussed and, if possible, integrated into models.

Accessing Gene Expression in Treatment-Resistant Schizophrenia - Patricia N. Moretti; Vanessa K. Ota; Eduardo S. Gouvea; Mariana Pedrini; Marcos L. Santoro; Fernanda Talarico; Leticia M. Spindola; Carolina Muniz Carvalho; Cristiano Noto; Gabriela Xavier; Elisa Brietzke; Ary Gadelha; et al. (Molecular Neurobiology, 2018)

Ground beetle (Coleoptera: Carabidae) communities on green roofs in Switzerland: synthesis and perspectives - Gaël Pétremand; Yannick Chittaro; Sonja Braaker; Stephan Brenneisen; Magdalena Gerner; Martin K. Obrist; Sophie Rochefort; Alexander Szallies; Marco Moretti (Urban Ecosystems, 2018)

Impacts of urban sprawl on species richness of plants, butterflies, gastropods and birds: not only built-up area matters - Elena D. Concepción; Martin K. Obrist; Marco Moretti; Florian Altermatt; Bruno Baur; Michael P. Nobis (Urban Ecosystems, 2016)

Afferent projections to the different medial amygdala subdivisions: a retrograde tracing study in the mouse - Bernardita Cádiz-Moretti; Marcos Otero-García; Fernando Martínez-García; Enrique Lanuza (Brain Structure and Function, 2016)

Towards soil water scarcity? An exploratory time-series analysis of the aridity index in Castelporziano forest, Rome - Luca Salvati; Valerio Moretti; Marco Zitti; Carlotta Ferrara (Rendiconti Lincei. Scienze Fisiche e Naturali, 2015)

Plant functional traits reveal the relative contribution of habitat and food preferences to the diet of grasshoppers - Sébastien Ibanez; Olivier Manneville; Christian Miquel; Pierre Taberlet; Alice Valentini; Serge Aubert; Eric Coissac; Marie-Pascale Colace; Quentin Duparc; Sandra Lavorel; Marco Moretti (Oecologia, 2013)

Can a trait-based multi-taxa approach improve our assessment of forest management impact on biodiversity? - Isabelle Aubin; Lisa Venier; Jennie Pearce; Marco Moretti (Biodiversity and Conservation, 2013)

Evaluation of viral load in infants hospitalized with bronchiolitis caused by respiratory syncytial virus - Carolina Scagnolari; Fabio Midulla; Carla Selvaggi; Katia Monteleone; Enea Bonci; Paola Papoff; Giulia Cangiano; Paola Di Marco; Corrado Moretti; Alessandra Pierangeli; Guido Antonelli (Medical Microbiology and Immunology, 2012)

Global patterns of stream detritivore distribution: implications for biodiversity loss in changing climates - Luz Boyero; Richard G. Pearson; David Dudgeon; Verónica Ferreira; Manuel A. S. Graça; Mark O. Gessner; Andrew J. Boulton; Eric Chauvet; Catherine M. Yule; Ricardo J. Albariño; Alonso Ramírez; Julie E. Helson; et al. (Global Ecology and Biogeography, 2012)
Aim We tested the hypothesis that shredder detritivores, a key trophic guild in stream ecosystems, are more diverse at higher latitudes, which has important ecological implications in the face of potential biodiversity losses that are expected as a result of climate change. We also explored the dependence of local shredder diversity on the regional species pool across latitudes, and examined the influence of environmental factors on shredder diversity. Location World‐wide (156 sites from 17 regions located in all inhabited continents at latitudes ranging from 67° N to 41° S). Methods We used linear regression to examine the latitudinal variation in shredder diversity at different spatial scales: alpha (α), gamma (γ) and beta (β) diversity. We also explored the effect of γ‐diversity on α‐diversity across latitudes with regression analysis, and the possible influence of local environmental factors on shredder diversity with simple correlations. Results Alpha diversity increased with latitude, while γ‐ and β‐diversity showed no clear latitudinal pattern. Temperate sites showed a linear relationship between γ‐ and α‐diversity; in contrast, tropical sites showed evidence of local species saturation, which may explain why the latitudinal gradient in α‐diversity is not accompanied by a gradient in γ‐diversity. Alpha diversity was related to several local habitat characteristics, but γ‐ and β‐diversity were not related to any of the environmental factors measured. Main conclusions Our results indicate that global patterns of shredder diversity are complex and depend on spatial scale. However, we can draw several conclusions that have important ecological implications. Alpha diversity is limited at tropical sites by local factors, implying a higher risk of loss of key species or the whole shredder guild (the latter implying the loss of trophic diversity). Even if regional species pools are not particularly species poor in the tropics, colonization from adjacent sites may be limited. Moreover, many shredder species belong to cool‐adapted taxa that may be close to their thermal maxima in the tropics, which makes them more vulnerable to climate warming. Our results suggest that tropical streams require specific scientific attention and conservation efforts to prevent loss of shredder biodiversity and serious alteration of ecosystem processes.

CWM and Rao’s quadratic diversity: a unified framework for functional ecology - Carlo Ricotta; Marco Moretti (Oecologia, 2011)

What is more important for invertebrate colonization in a stream with low-quality litter inputs: exposure time or leaf species? - Raphael Ligeiro; Marcelo S. Moretti; José Francisco Gonçalves; Marcos Callisto (Hydrobiologia, 2010)

Functional traits as indicators of biodiversity response to land use changes across ecosystems and organisms - Marie Vandewalle; Francesco de Bello; Matty P. Berg; Thomas Bolger; Sylvain Dolédec; Florence Dubs; Christian K. Feld; Richard Harrington; Paula A. Harrison; Sandra Lavorel; Pedro Martins da Silva; Marco Moretti; et al. (Biodiversity and Conservation, 2010)

Leaf abundance and phenolic concentrations codetermine the selection of case-building materials by Phylloicus sp. (Trichoptera, Calamoceratidae) - Marcelo S. Moretti; Rafael D. Loyola; Bárbara Becker; Marcos Callisto (Hydrobiologia, 2009)

Biodiversity and resilience of arthropod communities after fire disturbance in temperate forests - Marco Moretti; Peter Duelli; Martin K. Obrist (Oecologia, 2006)

Modelling the influence of change in fire regime on the local distribution of a Mediterranean pyrophytic plant species ( Cistus salviifolius ) at its northern range limit - Marco Moretti; Marco Conedera; Ruben Moresi; Antoine Guisan (Journal of Biogeography, 2006)
Aims To assess the potential distribution of an obligate seeder and active pyrophyte, Cistus salviifolius , a vulnerable species in the Swiss Red List; to derive scenarios by changing the fire return interval; and to discuss the results from a conservation perspective. A more general aim is to assess the impact of fire as a natural factor influencing the vegetation of the southern slopes of the Alps. Location Alps, southern Switzerland. Methods Presence–absence data to fit the model were obtained from the most recent field mapping of C. salviifolius . The quantitative environmental predictors used in this study include topographic, climatic and disturbance (fire) predictors. Models were fitted by logistic regression and evaluated by jackknife and bootstrap approaches. Changes in fire regime were simulated by increasing the time‐return interval of fire (simulating longer periods without fire). Two scenarios were considered: no fire in the past 15 years; or in the past 35 years. Results Rock cover, slope, topographic position, potential evapotranspiration and time elapsed since the last fire were selected in the final model. The Nagelkerke R 2 of the model for C. salviifolius was 0.57 and the Jackknife area under the curve evaluation was 0.89. The bootstrap evaluation revealed model robustness. By increasing the return interval of fire by either up to 15 years, or 35 years, the modelled C. salviifolius population declined by 30–40%, respectively. Main conclusions Although fire plays a significant role, topography and rock cover appear to be the most important predictors, suggesting that the distribution of C. salviifolius in the southern Swiss Alps is closely related to the availability of supposedly competition‐free sites, such as emerging bedrock, ridge locations or steep slopes. Fire is more likely to play a secondary role in allowing C. salviifolius to extend its occurrence temporarily, by increasing germination rates and reducing the competition from surrounding vegetation. To maintain a viable dormant seed bank for C. salviifolius , conservation managers should consider carrying out vegetation clearing and managing wild fire propagation to reduce competition and ensure sufficient recruitment for this species.

Evaluation of different protein sources in fingerling grey mullet Mugil cephalus practical diets - Umberto Luzzana; Franco Valfrè; Marco Mangiarotti; Cinzia Domeneghini; Giuseppe Radaelli; Vittorio Maria Moretti; Marco Scolari (Aquaculture International, 2005)

Clinical Epidemiology and Survival of Progressive Multifocal Leukoencephalopathy in the Era of Highly Active Antiretroviral Therapy: Data from the Italian Registry Investigative Neuro AIDS (IRINA) - Andrea Antinori; Antonella Cingolani; Patrizia Lorenzini; Maria Letizia Giancola; Ilaria Uccella; Simona Bossolasco; Susanna Grisetti; Francesca Moretti; Beniamino Vigo; Marco Bongiovanni; Bruno Del Grosso; Maria Irene Arcidiacono; et al. (Journal of NeuroVirology, 2003)